Cohesion in TIME Magazine Article “How covid-19 will shape the class of 2020 for the rest of their live” - Setyo Prasiyanto Cahyono; Valentina Widya Suryaningtyas; Raden Arief Nugroho (Universitas Dian Nuswantoro, 2020)
Abstract. This study is aimed at investigating the types of cohesive devices and their relationship which are found in an article of Time magazine entitled “how covid-19 will shape the class of 2020 for the rest of their live”. In conducting this study, the researchers employ descriptive qualitative as the research design. Meanwhile, in collecting the data, the researcher applied a purposive sampling method by choosing an article in an on line Time magazine. Meanwhile, the text was analyzed using systemic functional linguistics (SFL) especially those contributing to the cohesion of the text, including grammatical and lexical cohesion. The result of this study reveals that the text is “hang-together” which is described by the successfully use of cohesive devices. These patterns indicate that the writer of the article introduces the capacity to create a text with cohesion not only at the clause level but also to create text with better unity, flow and connectedness of information of the whole text. Besides, the use of cohesion in the text can create a relationship between language elements. Furthermore, the text of the article uses some simple cohesive devices such as reference, conjunction, repetition, and synonym.Keywords: cohesion, cohesive devices, language elements, magazine, SFLAbstrak. Penelitian ini bertujuan untuk menyelidiki jenis perangkat kohesif dan keterkaitannya dalam artikel majalah Time berjudul “how covid-19 will shape the class of 2020 for the rest of their live”. Dalam penelitian ini, peneliti menggunakan metode deskriptif kualitatif. Sedangkan dalam pengumpulan data, peneliti menggunakan sampel purposive dengan memilih artikel di majalah on line Time. Sedangkan teks dianalisis dengan menggunakan linguistik fungsional sistemik (LFS) terutama yang berkontribusi pada kohesi teks, termasuk kohesi gramatikal dan leksikal. Hasil penelitian ini menunjukkan bahwa teks yang dihasilkan oleh penulis “saling terpadu” yang digambarkan dengan berhasilnya penggunaan elemen perangkat kohesif. Pola-pola ini menunjukkan bahwa penulis artikel memunculkan kapasitas untuk membuat teks dengan kohesi tidak hanya pada tingkat klausa tetapi juga untuk membuat teks dengan kesatuan, aliran, dan keterhubungan informasi yang lebih baik dari keseluruhan teks. Selain itu penggunaan kohesi dalam teks dapat menciptakan hubungan antar elemen bahasa. Lebih lanjut lagi, teks tersebut menggunakan beberapa perangkat kohesif sederhana seperti referensi, konjungsi dan juga pengulangan, dan sinonim.Kata kunci: kohesi, peranti kohesi, unsur bahasa, LSF, majalah, perangkat kohesif